Implementación del sistema de contabilidad comercial, por el sistema de cuenta permanente y aplicación de Nic, en la boutique Metro Full Denim correspondiente al periodo mayo y junio 2016 - Camacho Jiménez, Katherine Lissette (2017)
The research work thesis "Implementation of commercial accounting system, BY THE SYSTEM OF PERMANENT ACCOUNT AND APPLICATION OF IAS 1, AT BOUTIQUE METRO FULL DENIM FOR THE PERIOD MAY AND JUNE 2016" provides insight accuracy and consistency management of financial - economic situation of the company, obtaining the presentation of its financial statements, based on International Accounting Standards that help optimize management. The objectives were fulfilled as the research was conducted, with updated and relevant to commercial accounting, just as information the accounting process it conducted with the supporting documentation provided by the owner, from the initial inventory of possessions until the financial statements for the system of permanent account and the respective analysis of IAS 1. After the thesis of the implementation of commercial accounting makes clear the importance of having found concrete solutions to the shortcomings identified in the accounting control allowing to have accurate and timely information on the progress of business information, recommending that the owner accept the proposal made in this investigative work, because through the organization and control of their resources you can get more useful.